Tracking the Covid zones through geo-fencing technique. Issue 5 (10th July 2020) - R., Anto Arockia Rosaline; R., Lalitha; G., Hariharan; N., Lokesh
Abstract : Purpose: Because of the outbreak of Covid 19, the entire world is thinking of new strategies, preventive measures to safeguard the human life from the widespread of the pandemic. The areas where people are affected are marked as containment zones and people are not allowed to exit out of those areas. Similarly, new people are not allowed to enter inside those areas. Hence, the purpose of this paper is to propose a methodology to track the Covid zones, to enhance and tighten the security measures. A geo-fence is created for the containment zone. The person who enters or exits out of that particular zone will be monitored and alert message will be sent to that person's mobile. Design/methodology/approach: After tracking the location of a suspicious individual, the geo-fenced layer is mapped in the area and then the virtual perimeter is used for further trapping process. This geo-fenced layer can be viewed by the citizens as soon as it is updated by the Covid monitoring team. The geo-fencing is a concept of building a virtual perimeter area. This virtual perimeter monitoring system helps in monitoring the containment zones effectively. It reduces operational costs by using an automated system based on wireless infrastructure. It also alerts the authorities immediately to catch the violators. Thus, it helps to speed up the process of inspecting the containment zones and monitoring the individuals who violate the rules given by government. Findings: The proposed methodologies will be an effective way to track the Covid's communal spread. But the workflow of the system demands the required data sets and permission in legal manner to set up the environment that maintains the constitutional law and order in practice. The application developed was a prototype to display how it works if the required data sets are provided by the government. There are several tracking models that are released across the world such as Aarogya setu (India), Trace together (Singapore) and Hagmen (Israel). All these models are based on Bluetooth proximity identification; though Bluetooth proximity identification is helpful for high range in a short distance, the privacy concern is debatable one. Using modern technology, it is so easy to crack the individual gadgets and with Bluetooth enabling it makes things even worse. Thus, it is important to maintain the tracking a safer and secure one, and another issue with those Bluetooth-based applications is that tracking can be done only if the user enabled the Bluetooth option, if not the entire functioning would become a mess. The proposed methodology of tracking without Bluetooth will ensure data security also. Originality/value: This was developed as a project by our third-year students of the Department of Information Technology of our college.